Análise da postura do tronco durante a marcha e a corrida em esteira subaquática - Thon, Regina Alves (2013)
Throughout life, humans constantly adapt themselves to different ways of locomotion and adopt several dynamic postures. Both gait and running set a complex interaction for muscle mechanisms; biomechanics leads us to a better comprehension on the variables concerning posture parameters for such practices. This descriptive study aimed at analyzing trunk posture for subjects both adapted and non-adapted to underwater treadmill during gait and running. Fifteen subjects divided into two groups took part in this study: Group (G1) seven students (runners) non-adapted to underwater treadmill and Group (G2) eight adapted (students) who practice underwater treadmill. Videogrametry was used in order to collect data for trunk biomechanics during both gait and running (NEUMANN, 2005). During collection procedures, volunteers conducted both gait and running on an underwater treadmill for an adaptation period of four minutes, at initial speed of 3,5Km/h, after this period, 0.4 Km/h were added to ten other speeds up to 7.5 km/h. Images were digitalized through Pinnacle Studio Plus software, version 9.4 and were subsequently treated through Dvideow software. Results: meaningful differences were found in trunk oscillations for sagittal, frontal and transverse planes concerning their angle amplitudes due to locomotion speed for each group; meaningful differences were also found for angle parameters when the groups were compared to one another. We conclude that trunk oscillations presented different behaviors for adapted and non-adapted subjects, pointing to complex task in a liquid environment.